Investigation of Relationship between Occupational Stress and Cardiovascular Risk Factors among Nurses - Amin SABERINIA; Anna ABDOLSHAHI; Saeed KHALEGHI; Yaser MORADI; Hossein JAFARIZADEH; Ali SADEGHI MOGHADDAM; Mohsen AMINIZADEH; Mehdi RAEI; Alireza KHAMMAR; Mohsen POURSADEQIAN (Iranian Journal of Public Health, 2020)
Background: One of the major causes of various work-related health problems among nurses is occupational stress. Hence, the main purpose of the present research was to find association between occupational stress of nurses and risk factors of cardiovascular disease.